Inequality and macroeconomic factors: A time-series analysis for a set of OECD countries - Virginia Maestri; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2012)
In this work, we study the short- and long-run properties of different inequality series vis-à-vis the most important macroeconomic series for a set of OECD countries. We employ standard tools of time series macro-econometrics (e.g. stationarity tests, detrending, co-movements analysis, Granger-causality tests, etc.) in order to possible uncover some fresh stylized facts about inequality. The broad picture emerging from our empirical analysis is one where some common patterns coexist together with several country specificities. More specifically, most of inequality series are not stationary; long-run equilibrium relationships between share prices and inequality emerge in Canada, the U.S., and the U.K.; at the business cycle frequencies, most inequality series are counter-cyclical (with the exception of Germany), negatively correlated with inflation and positively correlated with unemployment; consumption inequality is counter-cyclical in Europe, whereas pro-cyclical in English-speaking countries; the comovements between inequality series and government consumption appear to be heavily dependent on the institutions of the countries under analysis; Granger-causality tests suggest that in some cases inequality Granger-causes output.
Keywords: C10; D3; E32; 330; inequality; business cycles; detrending; cross-correlations; non-stationarity; cointegration; Granger causality tests; Einkommensverteilung; Konjunktur; Kointegration; Kausalanalyse; OECD-Staaten